Developing an innovative retail concept to showcase the smart home of the future - DA SILVA, Geoffrey (Institutional Knowledge at Singapore Management University, 2020)
In 2018, after nearly two decades of success in the highly competitive consumer electronics market of Singapore, Asian Home Electronics (AHE) Limited was once again searching for new frontiers to break through for its retail business. Having evolved from the traditional brick-and-mortar business model to omni-channel and to experiential retail, AHE, a household name consisting of five retail stores in the city-state, had set its eyes on retailing solutions for the smart home of the future. The vision of a smart home was beginning to come together as worldwide sales of smart devices reached an all-time high in 2016, and the industry was poised for even stronger growth in the next decade. However, the smart home concept had not been as pervasive as imagined several years ago. While it may appear exciting to many people, the wide array and the complications of operating smart home devices are also daunting to the average consumer. To bridge the gap between technology and consumers, retailers, such as AHE, are in the best position to demystify the complexity surrounding the smart home concept. To address the challenges that might confront a new entrant in the smart home market, AHE solicited ideas from consultancy companies through a call for proposals. Three shortlisted submissions presented a myriad of ideas in crafting a smart home retail concept, and AHE would need to carefully evaluate them based on two key criteria: first, how well did the consultant proposals present the smart home concept to consumers through the communication of multiple product inter-operability and overall retail store design? Secondly, what kind of recruitment and training would be effective in transitioning salespeople to become smart home advisors? This case study adopted the retailer’s perspective to understand an omni-channel approach in selling smart home solutions.